Encapsulation of Alpha-Lipoic Acid in Functional Hybrid Liposomes: Promising Tool for the Reduction of Cisplatin-Induced Ototoxicity - Manuela Curcio; Giuseppe Cirillo; Rosario Amato; Lorenzo Guidotti; Diana Amantea; Michele De Luca; Fiore Pasquale Nicoletta; Francesca Iemma; Mercedes Garcia-Gil (MDPI AG, 2022)
In this study, in order to address the drawback of cisplatin (CDDP)-induced ototoxicity, we propose a straightforward strategy based on the delivery of a sulfur-based antioxidant, such as lipoic acid (LA), to HEI-OC1 cells. To this aim, hybrid liposomes (LA@PCGC) with a spherical shape and a mean diameter of 25 nm were obtained by direct sonication of LA, phosphatidylcholine and a gelatin-curcumin conjugate in a physiological buffer. LA@PCGC were found to be stable over time, were quickly (i.e., by 1 h) taken up by HEI-OC1 cells, and guaranteed strong retention of the bioactive molecule, since LA release was less than 20%, even after 100 h. Cell viability studies showed the efficiency of LA@PCGC for stabilizing the protective activity of LA. Curcumin residues within the functional liposomes were indeed able to maintain the biological activity of LA, significantly improving (up to 2.19-fold) the viability of HEI-OC1 cells treated with 5 μM CDDP. Finally, LA@PCGC was incorporated within an alginate-based injectable hydrogel carrier to create a formulation with physical chemical features suitable for potential ear applications.